Sketchnote Components, Design Space Dimensions, and Strategies for Effective Visual Note Taking - Zheng, Rebecca; Camporro, Marina Fernández; Romat, Hugo; Henry Riche, Nathalie; Bach, Benjamin; Chevalier, Fanny; Hinckley, Ken; Marquardt, Nicolai (CHI '21: Proceedings of the 2021 CHI Conference on Human Factors in Computing Systems, 2021)
Sketchnoting is a form of visual note taking where people listen to, synthesize, and visualize ideas from a talk or other event using a combination of pictures, diagrams, and text. Little is known about the design space of this kind of visual note taking. With an eye towards informing the implementation of digital equivalents of sketchnoting, inking, and note taking, we introduce a classification of sketchnote styles and techniques, with a qualitative analysis of 103 sketchnotes, and situated in context with six semi-structured follow up interviews. Our findings distill core sketchnote components (content, layout, structuring elements, and visual styling) and dimensions of the sketchnote design space, classifying levels of conciseness, illustration, structure, personification, cohesion, and craftsmanship. We unpack strategies to address particular note taking challenges, for example dealing with constraints of live drawings, and discuss relevance for future digital inking tools, such as recomposition, styling, and design suggestions.